Stable-jet length controlling electrospun fiber radius: Model and experiment. (10th October 2019) - Lei, Sailing; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Abstract: Generally, the precise prediction and control on the radius of electrospun polymer fibers is critical for their applications but still remains challenging. In the current work, a model has been established to predict the radius. It is shown that the correlation between the stable-jet length and the terminal fiber radius satisfies a scaling law with a power exponent −2/3 for fully charged fibers, while the exponent becomes smaller for the case in which the fibers are partly charged on surface during electrospinning. And a good agreement between the experimental and theoretical values for electrospinning poly(methyl methacrylate) (PMMA) fibers is obtained, thus further verifying the correctness of derived model between the stable-jet length and the terminal fiber radius. Graphical abstract: Image 1 Highlights: An exponential model between stable-jet length and fiber radius is established. The scaling exponent is −2/3 for fully charged fibers in electrospinning. The scaling exponent becomes smaller, when the fibers are partly charged. The model can precisely predict and control the diameters of electrospun fibers.